Safety and immunogenicity of the recombinant BCG vaccine VPM1002 in a phase 1 open-label randomized clinical trial - Grode, Leander; Ganoza, Christian A.; Brohm, Christiane; Weiner, January; Eisele, Bernd; Kaufmann, Stefan H.E. (Vaccine, 2013)
► The recombinant BCG vaccine VPM1002 was tested in PPD+ and PPD− individuals. ► VPM1002 successfully completed a phase I clinical trial. ► VPM1002 was as safe as BCG. ► VPM1002 and BCG induced both shared and differential immune responses. Current vaccination using Mycobacterium bovis bacillus Calmette-Guérin (BCG), fails to prevent pulmonary tuberculosis (TB). New vaccination strategies are essential for reducing the global incidence of TB. We assessed the safety and immunogenicity of VPM1002, a recombinant BCG vaccine candidate. EudraCT (2007-002789-37) and ClinicalTrials.gov (NCT00749034). Healthy volunteers were enrolled in a phase 1 open-label, dose escalation randomized clinical trial, and received one intradermal dose of VPM1002 (Mycobacterium bovis BCG ΔureC::hly HmR) or BCG. Immunogenicity was assessed by interferon-gamma (IFN-γ) production, cellular immune response markers by flow cytometry and serum antibodies against mycobacterial antigens. Eighty volunteers were randomized into two groups according to previous BCG vaccination and mycobacterial exposure (BCG-naïve, n=40 and BCG-immune, n=40). In each group, 30 individuals were vaccinated with VPM1002 (randomized to three escalating doses) and 10 with BCG. VPM1002 was safe and stimulated IFN-γ-producing and multifunctional T cells, as well as antibody-producing B cells in BCG-naïve and BCG-immune individuals. VPM1002 was safe and immunogenic for B-cell and T-cell responses and hence will be brought forward through the clinical trial pipeline.